Triassic Revolution - Benton, Michael J.; Wu, Feixiang (Frontiers in Earth Science, 2022)
The Triassic has long been recognized as a time during which marine and terrestrial ecosystems modernized dramatically, and it seems to have been a two-step process. First, recovery from the Permian-Triassic mass extinction (PTME) was a time of extraordinary renewal and novelty, and these processes of change were enhanced, it seems, by the effects of the Carnian Pluvial Episode (CPE). After the CPE, in the oceans, not only did the carbonate factory begin to change towards its modern form, but also arguably the Mesozoic Marine Revolution (MMR) speeded up. When the MMR was proposed it was seen as a process that occurred in the Late Jurassic and Cretaceous, as modern crustaceans, gastropods, and fishes enhanced predator-prey arms races. New evidence from China and elsewhere suggests in fact the MMR was already underway in the Middle and Late Triassic, and so was coincident with Sepkoski’s classic idea that Paleozoic faunas were replaced by Modern marine faunas from the beginning of the Triassic. On land, ongoing competition between synapsids and archosauromorphs through the Triassic was marked by a posture shift from sprawling to erect, and a shift in physiology to warm-bloodedness, with insulating skin coverings of hair and feathers. Dinosaurs, for example, originated in the Early or Middle Triassic, but did not diversify until after the CPE. These arms races, the MMR in the sea, and the endothermy shift in tetrapods, were triggered by the PTME, and then enhanced by the CPE.